2022
DOI: 10.3390/jcm11102679
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Non-Union after Open Reduction and Internal Fixation in Patients with Distal Humerus Fractures

Abstract: Background: Only a few studies have reported on the risk factors for non-union after open reduction and internal fixation (ORIF) in distal humerus fractures. Methods: We retrospectively reviewed 155 patients who underwent ORIF for distal humerus fractures from January 2008 to June 2020. Various patient factors, including body mass index (BMI), diabetes mellitus (DM), and combined fracture, as well as surgical factors, including fixation methods (e.g., orthogonal plate/parallel plate/single plate/tension bend w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Tsai et al 50 found that sex was not associated with fracture healing. Ku et al 51 analyzed the risk factors for non-union in patients with distal humeral fractures after open reduction and internal fixation and found that BMI was not a statistically significant factor, a finding that is consistent with the results of this study. Cheng et al 52 confirmed that serum albumin level affects fracture healing; however, we did not obtain similar results after including it.…”
Section: Discussionsupporting
confidence: 90%
“…Tsai et al 50 found that sex was not associated with fracture healing. Ku et al 51 analyzed the risk factors for non-union in patients with distal humeral fractures after open reduction and internal fixation and found that BMI was not a statistically significant factor, a finding that is consistent with the results of this study. Cheng et al 52 confirmed that serum albumin level affects fracture healing; however, we did not obtain similar results after including it.…”
Section: Discussionsupporting
confidence: 90%
“…After distal humerus injury, there was a large number of local bone defect, and there was a risk of delayed or even non-union (31,32). Some studies have shown that the delay fracture recovery rate could reach 2%-10% after ORIF (33).…”
Section: Discussionmentioning
confidence: 99%
“…It is known, however, that stabilization should provide stable-enough fixation to obtain a union. It also should allow for an early rehabilitation process, as movement is essential for success in the final treatment due to the fact that the elbow is intolerant to immobilization [11][12][13].…”
Section: Introductionmentioning
confidence: 99%